The next wave using digital technology to further social and political innovation - West, Darrell M. 1954- (A Brookings focus book, 2011)
"Maintains that the digital revolution is well under way and will continue to lead to important changes in the way people, the for-profit and nonprofit sectors, and government will function and interact, with emphasis on the importance of innovation and the need to balance innovation, privacy, and security"--Provided by publisher.